Iterative UI/UX Design in Environmental Social Governance Website Development: A Case Study of Financial Park Labuan SDN. BHD. - Bagaskara Rahadi Putra; Husin, Nanang (Journal of Digital Business and Innovation Management, 2025)
This study aims to develop an interactive and responsive Environmental, Social, and Governance (ESG) website grounded in User Interface and User Experience (UI/UX) design principles to improve transparency, reporting efficiency, and stakeholder engagement at Financial Park Labuan Sdn. Bhd. The company is currently facing challenges in maintaining its competitiveness due to increasing demands for effective ESG implementation and communication. To address these issues, the development process adopted the Prototyping-based System Development Life Cycle (SDLC), allowing iterative testing and refinement based on user feedback. A quantitative approach was employed using surveys to evaluate user satisfaction and website usability. The findings from the survey revealed that the newly developed ESG website significantly enhances the accessibility of ESG-related information, strengthens stakeholder trust, and fosters active community engagement in sustainability initiatives. These outcomes suggest that incorporating user-centered digital solutions can support corporate efforts in meeting ESG standards while also improving public perception and organizational performance.